If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x)(x + 1) = 14(2x + 1) + 44 Reorder the terms: x(1 + x) = 14(2x + 1) + 44 (1 * x + x * x) = 14(2x + 1) + 44 (1x + x2) = 14(2x + 1) + 44 Reorder the terms: 1x + x2 = 14(1 + 2x) + 44 1x + x2 = (1 * 14 + 2x * 14) + 44 1x + x2 = (14 + 28x) + 44 Reorder the terms: 1x + x2 = 14 + 44 + 28x Combine like terms: 14 + 44 = 58 1x + x2 = 58 + 28x Solving 1x + x2 = 58 + 28x Solving for variable 'x'. Reorder the terms: -58 + 1x + -28x + x2 = 58 + 28x + -58 + -28x Combine like terms: 1x + -28x = -27x -58 + -27x + x2 = 58 + 28x + -58 + -28x Reorder the terms: -58 + -27x + x2 = 58 + -58 + 28x + -28x Combine like terms: 58 + -58 = 0 -58 + -27x + x2 = 0 + 28x + -28x -58 + -27x + x2 = 28x + -28x Combine like terms: 28x + -28x = 0 -58 + -27x + x2 = 0 Factor a trinomial. (-2 + -1x)(29 + -1x) = 0Subproblem 1
Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2Subproblem 2
Set the factor '(29 + -1x)' equal to zero and attempt to solve: Simplifying 29 + -1x = 0 Solving 29 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-29' to each side of the equation. 29 + -29 + -1x = 0 + -29 Combine like terms: 29 + -29 = 0 0 + -1x = 0 + -29 -1x = 0 + -29 Combine like terms: 0 + -29 = -29 -1x = -29 Divide each side by '-1'. x = 29 Simplifying x = 29Solution
x = {-2, 29}
| x+786(y+z)=2526 | | 129-4x=4x+9 | | -6-4x=15-9x | | x+3x-3= | | x+2y=128 | | 2x-3x+1+8x=2x+5+4x-3 | | (x-5)(x).5=42 | | 6-8x=3-9x | | 4x+18=14x-62 | | (3x+5)(8x-2)=(3x)(8x)+(3x)(-2)+(5)(8x)+(5)(-2) | | 9x+28=4x+103 | | 49-3x=8x+19 | | 2x+3y-5z=1 | | 6x-5=8+5x | | 5x+4=4x+4 | | X+7=34 | | 2x+10=4x-4 | | 408=10x+22 | | 3(y+6)-y=2(y-9) | | 2(5-x)=4x | | (2x+5)(4x-2)=(2x)(4x) | | (2x+5)(4x-2)=(2x)(4x)+(2x)(-2)+(5)(4x)+(5)(-2) | | -15x^2+11x-2=0 | | 12x^2+13x-30=0 | | 6x^2-11x+2=0 | | ln(x)-ln(x-7)=ln(2) | | ln(x)-ln(x-7)=ln(2) | | 30r^2-13r-3=0 | | 30t^2-49t+20=0 | | 589270957349857476-4= | | 12x^2+5-23x=0 | | 3(4x+5)=63 |